Calcium chelation: a novel approach to reduce cryopreservation‐induced damage to frozen platelets. Issue 7 (22nd April 2020) - Waters, Lauren; Padula, Matthew P.; Marks, Denese C.; Johnson, Lacey
Abstract : BACKGROUND: Cryopreserved platelets are phenotypically and functionally different to conventionally stored platelets. Calcium may be released from internal stores during the freeze–thaw process, initiating signaling events which lead to these alterations. It was hypothesized that the addition of a calcium chelator prior to cryopreservation may mitigate some of these changes. METHODS: Buffy coat–derived platelets that had been pooled and split were tested fresh and following cryopreservation (n = 8 per group). Platelets were cryopreserved using 5%‐6% dimethylsulfoxide (DMSO) or were supplemented with increasing concentrations of the internal calcium chelator, BAPTA‐AM (100 μM, 200 μM, or 400 μM), prior to storage at −80°C. RESULTS: Supplementation of platelets with BAPTA‐AM prior to freezing improved platelet recovery in a dose response manner (400 μM: 84 ± 2%) compared to standard DMSO cryopreserved platelets (70 ± 4%). There was a loss of GPIbα, GPVI, and GPIIb/IIIa receptors on platelets following cryopreservation, which was rescued when platelets were supplemented with BAPTA‐AM (400 μM: p < 0.0001 for all). Platelet activation markers, such as phosphatidylserine and P‐selectin, were externalized on platelets following cryopreservation. However, the addition of BAPTA‐AM significantly reduced the increase of these activation markers on cryopreserved platelets (400 μM: p < 0.0001 for both). Both cryopreserved platelet groups exhibited similar functionality as assessed by thromboelastography, forming clots at a faster rate than fresh platelets. CONCLUSIONS: This study demonstrates that calcium plays a crucial role in mediating cryopreservation‐induced damage to frozen platelets. The addition of the calcium chelator, BAPTA‐AM, prior to cryopreservation reduces this damage.